How to Determine whether Regional Markets are Integrated? Theory and Evidence from European Electricity Markets - Georg Gebhardt; Felix Höffler (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
Prices may di er between regional markets if transport capacities are limited. We develop a new approach to determine to which extent such di erences stem from limited participation in cross-border trader rather than from bottlenecks. We derive a theoretical integration benchmark for the typical case where transportation markets clear before the product markets, using Grossman's (1976) notion of a rational expectations equilibrium. We compare the benchmark to data from European electricity markets. The data reject the integration hypothesis: Capacity prices contain too little information about spot price di erential; this indicates that well informed traders do not engage in cross-border trade.
urn:nbn:de:bvb:19-epub-13316-5
Keywords: G14; D84; L94; 330; Market integration; electricity markets; interconnector; competition policy; rational expectations equilibrium